2016
DOI: 10.1542/peds.2015-3868
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Outcomes of Intrauterine Growth Restriction School-Age Children

Abstract: CONTEXT: Children who experienced intrauterine growth restriction (IUGR) may be at increased risk for adverse neurologic developmental outcomes during the school-age years of life. OBJECTIVE:To estimate the effect of IUGR on cognition and behavior in school-aged children.DATA SOURCES: Medline, Embase, and PsycINFO were searched for English-language articles published after 1980.DATA SELECTION We included case-control studies reporting cognitive and/or behavioral data of children who had IUGR and were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…However, one other review reported lower verbal and performance intelligence quotient scores in school‐age children born SGA 51 and neuroimaging studies have shown early microstructural changes related to altered neurobehavioral outcomes 52. We found consistently positive associations between postnatal growth and neurocognitive outcomes in four of the five observational studies included in the review 51. Interestingly, the only RCT included in this review reported a negative effect of growth induced by nutrient‐ and energy‐enriched formula feeding on developmental scores at nine months in just girls, but no differences between nutritional groups at 18 months.…”
Section: Discussionmentioning
confidence: 97%
“…However, one other review reported lower verbal and performance intelligence quotient scores in school‐age children born SGA 51 and neuroimaging studies have shown early microstructural changes related to altered neurobehavioral outcomes 52. We found consistently positive associations between postnatal growth and neurocognitive outcomes in four of the five observational studies included in the review 51. Interestingly, the only RCT included in this review reported a negative effect of growth induced by nutrient‐ and energy‐enriched formula feeding on developmental scores at nine months in just girls, but no differences between nutritional groups at 18 months.…”
Section: Discussionmentioning
confidence: 97%
“…There is some published evidence on the long-term outcomes of children born preterm, and most studies show that adverse outcomes are strongly associated with prematurity, mainly in the neurologic and behavioral fields (31). Further analysis seems to establish an important relationship between LBW and impaired development, making it a more important contributing factor than gestational age at delivery among others, although the association is not very strong and several studies await longer-term results (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Pluchino et al (2016), hypothesized that an altered progesterone/allopregnanolone fetal brain, during placental insufficiency, may result in behavioral consequences. IUGR may be at increased risk of having low cognitive scores in school-age (Chen et al, 2016).…”
Section: Placental Insufficiencymentioning
confidence: 99%